Ionospheric Scintillation Fading Coefficients for the GPS L1, L2, and L5 Frequencies - Moraes, Alison de O.; Vani, Bruno C. [UNESP]; Costa, Emanoel; Sousasantos, Jonas; Abdu, Mangalathayil A.; Rodrigues, Fabiano; Gladek, Yuri C.; Oliveira, Cesar B. A. de; Galera Monico, Joao F. [UNESP] (Amer Geophysical Union, 2018)
The terrestrial ionosphere over low-latitude regions presents the unique phenomena of the equatorial ionization anomaly (characterized by global maximum in plasma concentration) and plasma-depleted regions known as equatorial plasma bubbles and associated smaller-scale plasma irregularities. Transionospheric radio signals such as those from Global Navigation Satellite Systems constellations, traveling across this ambient, may suffer severe scintillation in amplitude and phase due to these plasma structures. Presently, three civilian signals available for GPS users, at L1 (1575.42MHz), L2C (1227.60MHz), and L5 (1176.45MHz) are used to investigate the propagation effects due to these irregularities. The purpose of the present work is to evaluate statistically the distribution of severe fade events for each of these carrier frequencies based on the nonlinear ionospheric propagation effects as represented by the fading coefficients of - distribution. The results from the analyses of data sets recorded by stations at different geomagnetic latitude locations in Brazil show that regions closer to the equatorial ionization anomaly crest present higher probability of severe fade events. Additionally, the L5 signals, dedicated for safety-of-life applications, revealed more unfavorable results when compared to the L1 and L2C frequencies. The results further showed that for 0.8S(4)1.0 the probabilities of fades deeper than -10dB were between 8.0% and 6.5% depending on the station position. Considering the case of fades deeper than -20dB, the results reach values near 1%, which is quite concerning. These results show empirically the fading environment that users of the new civilian signals may experience in low-latitude region. Additionally, the fading coefficients may help in the comprehension of the distribution of amplitude scintillation and its relation with the frequency used, aiding in the future the development of signal processing algorithms capable to mitigate errors for navigation users. This work shows differences in the statistics of GPS signals at different frequencies. The results warn that new signals will be more affected by the ionosphere in regions of low latitudes.
Keywords: ionospheric scintillation; fading coefficients; GNSS availability